REVOLUTION 4.0 IN UZBEKISTAN'S INDUSTRY: WAYS TO ENHANCE TECHNOLOGICAL INNOVATION AND COMPETITIVENESS - Shokhboz Kulmuratov (The Conference Hub, 2025)
This article explores the prospects and challenges of implementing the Industry 4.0 revolution in Uzbekistan’s industrial sector. It highlights the potential of digital transformation, automation, artificial intelligence (AI), and Internet of Things (IoT) technologies to modernize production processes, improve efficiency, and enhance the country’s industrial competitiveness. Drawing on global experiences, particularly from Germany and other developed economies, the study demonstrates how Industry 4.0 adoption can optimize production, improve product quality, and generate new employment opportunities. The research also analyzes the current state of Uzbekistan’s industry, identifying technological, economic, and workforce-related gaps that need to be addressed for successful implementation. Finally, the article emphasizes the strategic importance of integrating innovative technologies, workforce development, and digitalization in fostering sustainable economic growth and long-term industrial competitiveness in Uzbekistan.
Keywords: Digital transformation, Industry 4.0, automation, artificial intelligence, Internet of Things, industrial modernization, competitiveness, Uzbekistan, workforce development, innovation